2020
DOI: 10.20524/aog.2020.0477
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term outcomes of endoscopic submucosal dissection for non-ampullary duodenal neuroendocrine tumors

Abstract: Background Endoscopic resection is recommended for non-ampullary duodenal neuroendocrine tumors (NAD-NETs) ≤10 mm in diameter and confined to the submucosal layer, without lymph node or distant metastasis. However, the efficacy and safety of endoscopic submucosal dissection (ESD) for NAD-NET remains unclear. The aim of this study was to assess the short-term efficacy and safety and the long-term outcomes of ESD for NAD-NET.Methods Eight patients with 8 NAD-NETs who underwent ESD between 2015 and 2018 were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 38 publications
2
27
1
1
Order By: Relevance
“…5). However, the delayed bleeding rate in our study was higher than the previously reported rates for ESMR-L [5][6][7] and ESD [4,8,9]. Therefore, when performing prophylactic endoscopic coagulation of a mucosal defect to the fullest extent possible, even without bleeding immediately after resection, it is recommended that surgeons always perform a second endoscopy on the next day after EMRO.…”
Section: Discussioncontrasting
confidence: 67%
See 3 more Smart Citations
“…5). However, the delayed bleeding rate in our study was higher than the previously reported rates for ESMR-L [5][6][7] and ESD [4,8,9]. Therefore, when performing prophylactic endoscopic coagulation of a mucosal defect to the fullest extent possible, even without bleeding immediately after resection, it is recommended that surgeons always perform a second endoscopy on the next day after EMRO.…”
Section: Discussioncontrasting
confidence: 67%
“…Among the several endoscopic resections for DNETs reported, ESMR-L [5][6][7] and ESD [4,8,9] are the mainly used standard methods. In general, ESMR-L is considered technically easy, safe, and inexpensive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Immunohistochemistry is sensitive for detecting lymphovascular invasion and is recommended as an option in the ENETS guidelines 8 . In previous studies, the prevalence of lymphovascular invasion in nonampullary duodenal NETs treated with ER ranged from 0% to 10% 11,20,31–33 . There is a concern that the evaluation of lymphovascular invasion greatly differs depending on the presence of immunohistochemistry.…”
Section: Discussionmentioning
confidence: 99%